Principles of economethics from the Giffen demand - Franco, J. Agustín (Technological and Economic Development of Economy, 2015)
This paper raises an approach to the study of consumer behaviour and markets with a particular emphasis on agricultural commodities. It develops an analysis of demand for certain products during a recent economic recession in Spain by showing the behaviour of some of them as Giffen goods in some years. According to the theory of Giffen demand, there is a direct (positive) relationship between price and the quantity demanded. Thus, the income effect outweighs the substitution effect. The main contributions of this work can be summarized in the next three points: 1) This paper studies the consumer behaviour from a Giffen perspective, beyond a traditional and rational utility approach; 2) It also suggests a framework to analyse several socioeconomic proposals and theories related to the sustainability and Human Rights-based ethic level (intrinsic to Giffen behaviour); 3) Finally, this theory is a significant contribution to design better economic policies. The analysis of Giffen phenomenon has greater explanatory power than the classical theory of Marshall. It also helps to reveal a number of important effects that are usually ignored and that could contribute to clarify some current economic phenomena. First published online: 05 Feb 2014